Electrode slurry for lithium iron phosphate battery, preparation method of electrode slurry, positive plate, negative plate and lithium ion battery
By optimizing the composition and content of lithium iron phosphate and graphite battery slurry, the problems of cracking, uneven dispersion and large differences in surface density during homogenization and coating of the recovered materials are solved, and stable settlement and uniform dispersion of the slurry are achieved, with good compatibility and recycling effects.
Patent Information
- Application Number
- CN202411997536.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
When lithium iron phosphate and graphite recovered in the prior art are used in battery slurry, there are problems such as easy cracking of coating, uneven dispersion, scratches of large particles, and rapid settlement of the slurry, resulting in large surface density differences in coating during homogenization and coating.
By optimizing the composition and content of the positive electrode slurry and the negative electrode slurry, it includes adding a dispersant to the positive electrode slurry to increase the steric hindrance between the lithium iron phosphate particles, and adding a second organic solvent to the negative electrode slurry to improve the dispersion uniformity of the graphite particles.
During homogenization and coating, the slurry is stable settled and uniformly dispersed, avoiding cracking during coating and baking, and basically no difference in performance with the slurry using new materials, with good compatibility, promoting resource recycling and reducing raw material costs.
Smart Images

Figure BDA0005226092090000121 
Figure BDA0005226092090000122
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an electrode slurry for a lithium iron phosphate battery and a preparation method thereof, a positive electrode sheet, a negative electrode sheet, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are one of the most widely used power batteries. However, the average life of lithium-ion batteries is 5 to 10 years, and they contain a large number of various metal components and organic solvents that are harmful to the environment and human body. After they are scrapped, they will bring new environmental problems. At the same time, waste power lithium-ion batteries are rich in various valuable metal elements such as cobalt, manganese, nickel, lithium, etc. Therefore, in order to protect the environment and save resources, it is necessary to recycle lithium-ion battery materials to reduce the consumption of raw materials, thereby improving resource utilization, reducing production costs and environmental pollution.
[0003] The solid waste generated during the production of positive and negative electrode materials of traditional lithium-ion batteries mainly includes positive electrode materials, negative electrode materials, electrolytes and diaphragms, etc. These wastes contain a large amount of valuable metal elements and active substances. If they are directly discarded, it will not only cause a waste of resources, but also cause environmental pollution. At present, the recycling and treatment of lithium-ion batteries mainly recycles the metal elements (such as Li, Co, Ni, Cu and Al, etc.) and active substances that are easier to recycle in batteries, but the recycling and treatment of active substances in batteries is still less.
[0004] At present, the utilization rate of recycled positive electrode lithium iron phosphate and graphite materials for preparing lithium iron phosphate batteries is low, and the recycled active materials will encounter problems such as rapid increase in slurry viscosity, large sedimentation, coating cracking, surface density fluctuations and uneven dispersion leading to large particle scratches during slurrying and coating. Most of the screening and separation processes for scrapped poles use physical separation methods, and there is no carbonization coating of recycled graphite by mixing and re-calcining at high temperature. These reasons make the particle surface groups, carbon content and gram capacity of recycled materials differ greatly from those of new materials. Summary of the invention
[0005] The main purpose of the present application is to provide an electrode slurry for lithium iron phosphate batteries and a preparation method thereof, a positive electrode sheet, a negative electrode sheet, and a lithium-ion battery, so as to solve the problems in the prior art that when the recycled lithium iron phosphate and graphite are used in the battery slurry, there are problems such as easy cracking during the slurrying and coating process, uneven dispersion causing large particle scratches, and rapid sedimentation of the slurry causing large differences in the coating surface density.
[0006] In order to achieve the above-mentioned purpose, according to one aspect of the present application, there is provided an electrode slurry for a lithium iron phosphate battery, comprising a positive electrode slurry and a negative electrode slurry each independently, the positive electrode slurry comprising recycled lithium iron phosphate, and the negative electrode slurry comprising recycled graphite, wherein the recycled lithium iron phosphate and the recycled graphite come from the scraps of the positive and negative electrode sheets of the lithium iron phosphate battery respectively; in parts by weight, the positive electrode slurry comprises: 96.0 to 99.0 parts of recycled lithium iron phosphate, 0.4 to 2.0 parts of a first conductive agent, 0.4 to 2.0 parts of a first binder, 0.2 to 1.0 parts of a dispersant and a first organic solvent; in parts by weight, the negative electrode slurry comprises: 96.0 to 98.0 parts of recycled graphite, 0.4 to 2.0 parts of a second conductive agent, 0.8 to 2.2 parts of a second binder, 0.6 to 1.8 parts of a first thickener, a second organic solvent and water.
[0007] Furthermore, the surface of the recovered lithium iron phosphate contains a third conductive agent and a third binder; the mass proportion of the third conductive agent in the recovered lithium iron phosphate is 0.5-1.5%, and the mass proportion of the third binder in the recovered lithium iron phosphate is 0.8-2%; and / or, the surface of the recovered graphite contains a fourth binder and a second thickener; the mass proportion of the fourth binder in the recovered graphite is 0.1-2%, and the mass proportion of the second thickener in the recovered graphite is 0.1-1.6%.
[0008] Furthermore, the solid content of the positive electrode slurry is 56-68%, and / or the solid content of the negative electrode slurry is 48-54%; and / or, after the positive electrode slurry and the negative electrode slurry are respectively left to stand for 24 hours, the viscosity of the positive electrode slurry is 240000-400000 mPa·s, and the sedimentation rate of the positive electrode slurry is ≤4%, and / or, the viscosity of the negative electrode slurry is 3000-8000 mPa·s, and the sedimentation rate of the negative electrode slurry is ≤1.5%.
[0009] Furthermore, the first conductive agent and the third conductive agent are each independently selected from any one or more of conductive carbon black, acetylene black and carbon nanotubes; the first binder and the third binder are each independently selected from polyvinylidene fluoride and / or polyvinyl butyral; and / or, the dispersant includes a first dispersant and a second dispersant, the first dispersant is selected from any one or more of polyacrylic acid, polymethacrylic acid, polyester chain polymer, sodium silicate, polyoxyethylene ether, glycerol, sodium alginate and hydroxypropyl methylcellulose; the second dispersant is selected from any one or more of polyethylene glycol, sodium lauryl sulfate, polyvinyl pyrrolidone and polyurethane compounds; and / or, the mass ratio of the first dispersant to the second dispersant is 1 to 2.5:1.
[0010] Furthermore, the second conductive agent is selected from any one or more of conductive carbon black, acetylene black and carbon nanotubes; and / or the second binder and the fourth binder are each independently selected from any one or more of styrene-butadiene rubber, polyacrylic acid and water-based polyurethane; and / or the first thickener and the second thickener are each independently selected from any one or more of carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; and / or the second organic solvent is selected from any one or more of N-methylpyrrolidone, ethylene glycol, ethylene glycol ether compounds, dimethyl sulfoxide and propylene carbonate; and / or the mass ratio of the second organic solvent to the recovered graphite is 0.3-1.5:100; and / or the first organic solvent is N-methylpyrrolidone.
[0011] According to another aspect of the present application, a method for preparing the electrode slurry for the above-mentioned lithium iron phosphate battery is provided, and the method for preparing the positive electrode slurry comprises: subjecting the raw materials including recovered lithium iron phosphate, a first conductive agent, a first binder, a dispersant and a first organic solvent to a first stirring to obtain the positive electrode slurry; the method for preparing the negative electrode slurry comprises: subjecting the raw materials including recovered graphite, a second conductive agent, a second binder, a first thickener, a second organic solvent and water to a second stirring to obtain the negative electrode slurry.
[0012] Furthermore, the ratio of the mass of recovered lithium iron phosphate to the volume of the first organic solvent is 1.37-2.51 g / mL; and / or, the ratio of the mass of recovered graphite to the volume of water is 0.92-1.16 g / mL; and / or, the rotation speeds of the first stirring and the second stirring are each independently 300-1500 rpm.
[0013] According to another aspect of the present application, a positive electrode sheet is provided, comprising a current collector and a positive electrode active coating, wherein the positive electrode active coating is prepared from a positive electrode slurry, and the positive electrode slurry comprises the above-mentioned positive electrode slurry.
[0014] According to another aspect of the present application, a negative electrode sheet is provided, comprising a current collector and a negative electrode active coating, wherein the negative electrode active coating is prepared from a negative electrode slurry, and the negative electrode slurry comprises the above-mentioned negative electrode slurry.
[0015] According to another aspect of the present application, a lithium-ion battery is provided, including a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet includes the positive electrode sheet described above, and the negative electrode sheet includes the negative electrode sheet described above.
[0016] Applying the technical solution of the present application, for the lithium iron phosphate and graphite recovered by the physical method, the surfaces still contain a binder, and the binder on the surface of the recovered lithium iron phosphate can still exert most of the bonding properties under the condition of re-homogenization, and the binder on the surface of the recovered graphite can basically not exert its bonding properties. Therefore, the present application optimizes the composition and content of the positive electrode slurry and the negative electrode slurry so that the slurry is stably settled and evenly dispersed during the homogenization and coating process, and is not prone to cracking during the coating and baking process. At the same time, in terms of performance, the positive electrode slurry and the negative electrode slurry of the present application are basically the same as the slurry using the new materials lithium iron phosphate and graphite, and have good compatibility on the production equipment, which is conducive to resource recycling and reducing the cost of raw materials. Specifically, in the positive electrode slurry, adding a dispersant can not only increase the steric hindrance between the lithium iron phosphate particles, thereby preventing the lithium iron phosphate particles from agglomerating, but also enhance the stability of the lithium iron phosphate particles and adjust the viscosity and fluidity of the positive electrode slurry, thereby facilitating the stability of the positive electrode slurry surface density during the coating process. Adding the second organic solvent to the negative electrode slurry can effectively separate the recycled graphite particles, thereby improving the dispersion uniformity of the recycled graphite and reducing the occurrence of cracking of the negative electrode sheet. At the same time, adding the second organic solvent can fully dissolve the second binder and make it evenly distributed around the recycled graphite particles and the second conductive agent, thereby enhancing the bonding force between the recycled graphite particles, preventing the pulverization and shedding of the negative electrode material, and thus extending the cycle life of the battery. DETAILED DESCRIPTION
[0017] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0018] As analyzed in the background technology of this application, when the lithium iron phosphate and graphite recovered in the prior art are used for battery slurry, there are problems such as easy cracking of the coating, uneven dispersion resulting in scratches of large particles, and rapid sedimentation of the slurry resulting in large differences in the surface density of the coating during the homogenization and coating process. In order to solve the above problems, the present application provides an electrode slurry for lithium iron phosphate batteries and its preparation method, positive electrode sheet, negative electrode sheet, and lithium-ion battery.
[0019] In a typical embodiment of the present application, an electrode slurry for a lithium iron phosphate battery is provided, comprising a positive electrode slurry and a negative electrode slurry each independently, the positive electrode slurry comprising recycled lithium iron phosphate, and the negative electrode slurry comprising recycled graphite, wherein the recycled lithium iron phosphate and the recycled graphite come from the scraps of the positive electrode sheet and the negative electrode sheet of the lithium iron phosphate battery respectively; in parts by weight, the positive electrode slurry comprises: 96.0 to 99.0 parts of recycled lithium iron phosphate, 0.4 to 2.0 parts of a first conductive agent, 0.4 to 2.0 parts of a first binder, 0.2 to 1.0 parts of a dispersant and a first organic solvent; in parts by weight, the negative electrode slurry comprises: 96.0 to 98.0 parts of recycled graphite, 0.4 to 2.0 parts of a second conductive agent, 0.8 to 2.2 parts of a second binder, 0.6 to 1.8 parts of a first thickener, a second organic solvent and water.
[0020] For lithium iron phosphate and graphite recovered by physical method, their surfaces still contain binders, and the binder on the surface of lithium iron phosphate can still exert most of the bonding properties under the condition of re-homogenization, and the binder on the surface of graphite can basically not exert its bonding properties. Therefore, the present application optimizes the composition and content of the positive electrode slurry and the negative electrode slurry so that the slurry can be stably settled and evenly dispersed during homogenization and coating, and is not prone to cracking during coating and baking. At the same time, in terms of performance, the positive electrode slurry and negative electrode slurry of the present application are basically the same as the slurry using new materials lithium iron phosphate and graphite, and have good compatibility on production equipment, which is conducive to resource recycling and reducing raw material costs. Specifically, in the positive electrode slurry, adding a dispersant can not only increase the steric hindrance between the lithium iron phosphate particles, thereby preventing the lithium iron phosphate particles from agglomerating, but also enhance the stability of the lithium iron phosphate particles and adjust the viscosity and fluidity of the positive electrode slurry, thereby helping to ensure the stability of the positive electrode slurry surface density during coating. Adding the second organic solvent to the negative electrode slurry can effectively separate the recycled graphite particles, thereby improving the dispersion uniformity of the recycled graphite and reducing the occurrence of cracking of the negative electrode sheet. At the same time, adding the second organic solvent can fully dissolve the second binder and make it evenly distributed around the recycled graphite particles and the second conductive agent, thereby enhancing the bonding force between the recycled graphite particles, preventing the pulverization and shedding of the negative electrode material, and thus extending the cycle life of the battery.
[0021] In addition, the weight proportion of the recovered lithium iron phosphate can be 96.0 parts, 97.0 parts, 98.0 parts or 99.0 parts. Of course, the weight proportion of the recovered lithium iron phosphate can be any point value within the range of 96.0 to 99.0 parts, which will not be repeated here.
[0022] The weight fraction of the first conductive agent can be 0.4 parts, 0.5 parts, 1.0 parts, 1.5 parts or 2.0 parts. Of course, the weight fraction of the first conductive agent can be any value within the range of 0.4 to 2.0 parts, which will not be described in detail here.
[0023] The weight fraction of the first binder can be 0.4 parts, 0.5 parts, 1.0 parts, 1.5 parts or 2.0 parts. Of course, the weight fraction of the first binder can be any value within the range of 0.4 to 2.0 parts, which will not be described in detail here.
[0024] The weight percentage of the dispersant can be 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts or 1.0 parts. Of course, the weight percentage of the dispersant can be any point value within the range of 0.2 to 1.0 parts, which will not be repeated here.
[0025] The weight proportion of the recovered graphite can be 96.0 parts, 97.0 parts or 98.0 parts. Of course, the weight proportion of the recovered graphite can be any point value within the range of 96.0 to 98.0 parts, which will not be described in detail here.
[0026] The weight fraction of the second conductive agent can be 0.4 parts, 0.5 parts, 1.0 parts, 1.5 parts or 2.0 parts. Of course, the weight fraction of the second conductive agent can be any value within the range of 0.4 to 2.0 parts, which will not be described in detail here.
[0027] The weight fraction of the second binder can be 0.8 parts, 1.2 parts, 1.6 parts, 1.8 parts or 2.2 parts. Of course, the weight fraction of the second binder can be any point value within the range of 0.8 to 2.2 parts, which will not be repeated here.
[0028] The weight fraction of the first thickener can be 0.6 parts, 1.0 parts, 0.6 parts, 1.4 parts or 1.8 parts. Of course, the weight fraction of the first thickener can be any point value within the range of 0.6 to 1.8 parts, which will not be repeated here.
[0029] In one embodiment of the present application, the surface of the recovered lithium iron phosphate contains a third conductive agent and a third binder; the mass proportion of the third conductive agent in the recovered lithium iron phosphate is 0.5-1.5%, and the mass proportion of the third binder in the recovered lithium iron phosphate is 0.8-2%; and / or, the surface of the recovered graphite contains a fourth binder and a second thickener; the mass proportion of the fourth binder in the recovered graphite is 0.1-2%, and the mass proportion of the second thickener in the recovered graphite is 0.1-1.6%.
[0030] For the recycled lithium iron phosphate whose surface contains the third conductive agent and the third binder in the above-mentioned content, and the recycled graphite whose surface contains the fourth binder and the second thickener in the above-mentioned content, the present application optimizes the composition and content of the positive electrode slurry and the negative electrode slurry, which helps to stably settle and evenly disperse the slurry during the homogenization and coating process and is not prone to cracking during the coating and baking process.
[0031] In addition, the mass proportion of the third conductive agent in the recovered lithium iron phosphate can be 0.5%, 0.8%, 1.2% or 1.5%. Of course, the mass proportion of the third conductive agent in the recovered lithium iron phosphate can be any point value within the range of 0.5-1.5%, which will not be repeated here.
[0032] The mass proportion of the third binder in the recovered lithium iron phosphate can be 0.8%, 1.2%, 1.6% or 2%. Of course, the mass proportion of the third binder in the recovered lithium iron phosphate can be any point value within the range of 0.8-2%, which will not be repeated here.
[0033] The mass proportion of the fourth binder in the recycled graphite can be 0.1%, 0.5%, 1.0%, 1.5% or 2%. Of course, the mass proportion of the fourth binder in the recycled graphite can be any point value within the range of 0.1 to 2%, which will not be repeated here.
[0034] The mass proportion of the second thickener in the recovered graphite can be 0.1%, 0.5%, 1.0%, 1.3% or 1.6%. Of course, the mass proportion of the second thickener in the recovered graphite can be any point value within the range of 0.1 to 1.6%, which will not be repeated here.
[0035] In one embodiment of the present application, the solid content of the positive electrode slurry is 56-68%, and / or the solid content of the negative electrode slurry is 48-54%; and / or, after the positive electrode slurry and the negative electrode slurry are left to stand for 24 hours respectively, the viscosity of the positive electrode slurry is 240000-400000 mPa·s, and the sedimentation rate of the positive electrode slurry is ≤4%, and / or, the viscosity of the negative electrode slurry is 3000-8000 mPa·s, and the sedimentation rate of the negative electrode slurry is ≤1.5%.
[0036] It is preferred to control the solid content of the positive electrode slurry and the negative electrode slurry within the above range, which helps the active material particles to form a more compact and orderly arrangement structure during the coating process, thereby improving the uniformity and consistency of the coating, and thus reducing the risk of cracks in the coating during the drying process. At the same time, it helps the viscosity and sedimentation rate of the positive electrode slurry and the negative electrode slurry to reach the above range after standing for 24 hours, thereby minimizing the local structural defects of the electrode caused by particle sedimentation, thereby improving the consistency of the lithium-ion battery.
[0037] In addition, the solid content of the positive electrode slurry may be 56%, 60%, 64% or 68%. Of course, the solid content of the positive electrode slurry may be any point value within the range of 56-68%, which will not be described in detail here.
[0038] The solid content of the negative electrode slurry may be 48%, 50%, 52% or 54%. Of course, the solid content of the negative electrode slurry may be any point value within the range of 48-54%, which will not be described in detail here.
[0039] After the positive electrode slurry and the negative electrode slurry are left to stand for 24 hours respectively, the viscosity of the positive electrode slurry may be 240000 mPa·s, 260000 mPa·s, 275000 mPa·s, 294000 mPa·s, 340000 mPa·s, 375000 mPa·s or 400000 mPa·s. Of course, the viscosity of the positive electrode slurry may be any point value within the range of 240000 to 400000 mPa·s. The sedimentation rate of the positive electrode slurry may be 0.26%, 0.50%, 0.92%, 1.56%, 2.30%, 2.80%, 3.30%, 3.75% or 4%. Of course, the sedimentation rate of the positive electrode slurry may be any point value within the range of ≤4%. The viscosity of the negative electrode slurry may be 3000 mPa·s, 3500 mPa·s, 4000 mPa·s, 4800 mPa·s, 5700 mPa·s, 6980 mPa·s, 7500 mPa·s or 8000 mPa·s. Of course, the viscosity of the negative electrode slurry may be any point value within the range of 3000 to 8000 mPa·s. The sedimentation rate of the negative electrode slurry may be 0.22%, 0.45%, 0.56%, 0.74%, 1.15%, 1.25% or 1.5%. Of course, the sedimentation rate of the negative electrode slurry may be any point value within the range of ≤1.5%, which will not be described herein.
[0040] In one embodiment of the present application, the first conductive agent and the third conductive agent are each independently selected from any one or more of conductive carbon black, acetylene black and carbon nanotubes; the first binder and the third binder are each independently selected from polyvinylidene fluoride (PVDF) and / or polyvinyl butyral; and / or, the dispersant includes a first dispersant and a second dispersant, the first dispersant is selected from any one or more of polyacrylic acid, polymethacrylic acid, polyester chain polymer, sodium silicate, polyoxyethylene ether, glycerol, sodium alginate and hydroxypropyl methylcellulose; the second dispersant is selected from any one or more of polyethylene glycol, sodium lauryl sulfate, polyvinyl pyrrolidone and polyurethane compounds; and / or, the mass ratio of the first dispersant to the second dispersant is 1 to 2.5:1.
[0041] It is preferred to control the types of the first conductive agent and the third conductive agent within the above range, which helps to improve the conductivity of the positive electrode sheet. The types of the first conductive agent and the third conductive agent are consistent, which helps to further improve the conductivity of the positive electrode sheet. It is preferred to control the types of the first binder and the third binder within the above range, which helps to minimize the shedding of active materials, enhance the structural stability of the positive electrode sheet and reduce the internal resistance of the battery. The types of the first binder and the third binder are consistent, which is more conducive to further enhancing the structural stability of the positive electrode sheet.
[0042] It is preferred to control the type of the first dispersant within the above range, and the molecular chain structure it has helps to form an effective coating layer on the surface of the lithium iron phosphate particles. On the one hand, its chain structure helps to increase the steric hindrance between the lithium iron phosphate particles, thereby minimizing the agglomeration of the lithium iron phosphate particles due to their proximity to each other. On the other hand, the interaction between the first dispersant and the surface of the lithium iron phosphate particles helps to improve the dispersibility of the lithium iron phosphate particles in the slurry, so that more lithium iron phosphate particles can be accommodated, thereby increasing the solid content of the positive electrode slurry. It is preferred to control the type of the second dispersant within the above range, which helps to form a strong interaction with the surface of the lithium iron phosphate particles, thereby enhancing the stability of the lithium iron phosphate particles in the slurry, so that it is not easy to settle or stratify when it is standing or subjected to a certain external force. At the same time, the addition of the second dispersant helps to adjust the rheological properties of the positive electrode slurry, so that the positive electrode slurry has a suitable viscosity and fluidity, which is beneficial to the stability of the coating surface density during the coating process and improves the long-term storage capacity of the positive electrode slurry. It is preferred to control the mass ratio of the first dispersant to the second dispersant within the above range, which helps to further enhance the synergistic effect between the two, thereby further improving the dispersion uniformity of the lithium iron phosphate particles, improving the stability and solid content of the positive electrode slurry, thereby improving the coating performance, and further optimizing the consistency of the lithium-ion battery.
[0043] In addition, the mass ratio of the first dispersant to the second dispersant may be 1:1, 1.5:1, 2:1 or 2.5:1. Of course, the mass ratio of the first dispersant to the second dispersant may be any point value within the range of 1 to 2.5:1, which will not be elaborated here.
[0044] In one embodiment of the present application, the second conductive agent is selected from any one or more of conductive carbon black, acetylene black and carbon nanotubes; and / or, the second binder and the fourth binder are each independently selected from any one or more of styrene-butadiene rubber (SBR), polyacrylic acid and water-based polyurethane; and / or, the first thickener and the second thickener are each independently selected from any one or more of carboxymethyl cellulose (CMC), hydroxyethyl cellulose and polyvinyl alcohol; and / or, the second organic solvent is selected from any one or more of N-methylpyrrolidone, ethylene glycol, ethylene glycol ether compounds, dimethyl sulfoxide and propylene carbonate; and / or, the mass ratio of the second organic solvent to the recovered graphite is 0.3-1.5:100; and / or, the first organic solvent is N-methylpyrrolidone.
[0045] The type of the second conductive agent is preferably controlled within the above range, which helps to improve the conductivity of the negative electrode sheet. The types of the second binder and the fourth binder are preferably controlled within the above range, which helps to minimize the shedding of active materials and enhance the structural stability of the negative electrode sheet. The types of the first thickener and the second thickener are preferably controlled within the above range, which helps to adjust the viscosity of the negative electrode slurry and minimize sedimentation.
[0046] It is preferred to control the type of the second organic solvent and the mass ratio of the second organic solvent and the recovered graphite in the above range, which helps to further improve the dispersion effect, thereby helping to make the surface of the negative electrode plate after coating flat and the thickness uniform, which is conducive to the uniform embedding and extraction of lithium ions in the electrode, thereby improving the electrochemical performance of the lithium ion battery. Its main mechanism of action is that the second organic solvent molecules are adsorbed on the surface of the recovered graphite particles to form a solvation layer, which helps to reduce the mutual attraction between the recovered graphite particles. At the same time, the binder has good solubility in the second organic solvent, so that the binder molecules can be evenly distributed around the recovered graphite particles and the conductive agent, so as to better wrap around the recovered graphite particles, enhance the bonding force between the recovered graphite particles, and then stabilize the sedimentation of the negative electrode slurry as much as possible. It is preferred that the type of the first organic solvent is in the above range, which helps to recover the lithium iron phosphate and evenly disperse it in the first organic solvent, thereby improving the coating quality.
[0047] In addition, the mass ratio of the second organic solvent to the recovered graphite can be 0.3:100, 0.5:100, 1.0:100 or 1.5:100. Of course, the mass ratio of the second organic solvent to the recovered graphite can be any point value within the range of 0.3 to 1.5:100, which will not be repeated here.
[0048] In another typical embodiment of the present application, a method for preparing the above-mentioned electrode slurry is provided, and the method for preparing the positive electrode slurry comprises: subjecting the raw materials including recovered lithium iron phosphate, a first conductive agent, a first binder, a dispersant and a first organic solvent to a first stirring to obtain a positive electrode slurry; the method for preparing the negative electrode slurry comprises: subjecting the raw materials including recovered graphite, a second conductive agent, a second binder, a first thickener, a second organic solvent and water to a second stirring to obtain a negative electrode slurry.
[0049] By preparing the positive electrode slurry by the above-mentioned preparation method, on the one hand, the stable and uniform dispersion of the recovered lithium iron phosphate can be achieved, so that after 24h of sedimentation, the difference between the solid content of the upper positive electrode slurry and the lower positive electrode slurry is reduced from 10% to less than 1%, thereby ensuring the stability of the coating surface density during the coating process and improving the long-term storage capacity of the positive electrode slurry. On the other hand, the viscosity of the positive electrode slurry increases steadily during the first stirring process, and there will be no gel jelly-like and other unusable states. In addition, adding the first dispersant and the second dispersant can improve the dispersibility of the recovered lithium iron phosphate particles, thereby increasing the solid content of the positive electrode slurry and reducing the amount of the first organic solvent. By preparing the negative electrode slurry by the above-mentioned preparation method, adding the second organic solvent can not only make the recovered graphite particles evenly dispersed, thereby ensuring the flat surface and uniform thickness of the negative electrode sheet after coating, which is conducive to the uniform embedding and extraction of lithium ions in the electrode, thereby improving the electrochemical performance of the lithium ion battery. At the same time, after the binder is dissolved in the second organic solvent, it can be better wrapped on the surface of the recovered graphite particles, thereby enhancing the bonding force between the recovered graphite particles. In addition, the addition of the second organic solvent helps to lower the boiling point of the solvent water in the negative electrode slurry and increase the volatilization rate of the solvent water, thereby inhibiting the cracking of the negative electrode sheet.
[0050] In one embodiment of the present application, the ratio of the mass of recovered lithium iron phosphate to the volume of the first organic solvent is 1.37 to 2.51 g / mL; and / or, the ratio of the mass of recovered graphite to the volume of water is 0.92 to 1.16 g / mL; and / or, the rotational speeds of the first stirring and the second stirring are each independently 300 to 1500 rpm.
[0051] Preferably, the ratio of the mass of the recovered lithium iron phosphate to the volume of the first organic solvent and the speed of the first stirring are controlled within the above range, which helps to evenly disperse the recovered lithium iron phosphate in the first organic solvent, thereby improving the coating quality. Preferably, the ratio of the mass of the recovered graphite to the volume of water and the speed of the second stirring are controlled within the above range, which helps to evenly disperse the recovered graphite in the water, thereby improving the coating quality.
[0052] In addition, the ratio of the mass of recovered lithium iron phosphate to the volume of the first organic solvent can be 1.37 g / mL, 1.42 g / mL, 1.53 g / mL, 1.82 g / mL, 2.05 g / mL or 2.51 g / mL. Of course, the ratio of the mass of recovered lithium iron phosphate to the volume of the first organic solvent can be any point value within the range of 1.37 to 2.51 g / mL, which will not be repeated here.
[0053] The ratio of the mass of recovered graphite to the volume of water can be 0.92 g / mL, 1.02 g / mL, 1.04 g / mL, 1.10 g / mL or 1.16 g / mL. Of course, the ratio of the mass of recovered graphite to the volume of water can be any point value within the range of 0.92 to 1.16 g / mL, which will not be repeated here.
[0054] The rotation speeds of the first stirring and the second stirring can be 300 rpm, 600 rpm, 1000 rpm or 1500 rpm independently. Of course, the rotation speeds of the first stirring and the second stirring can be any point value within the range of 300 to 1500 rpm independently, which will not be repeated here.
[0055] In another typical embodiment of the present application, a positive electrode sheet is provided, including a current collector and a positive electrode active coating, wherein the positive electrode active coating is prepared from a positive electrode slurry, and the positive electrode slurry includes the above-mentioned positive electrode slurry.
[0056] The positive electrode sheet including the above-mentioned positive electrode slurry has good structural stability and electrochemical properties. At the same time, the peeling force of the positive electrode sheet reaches 0.2~0.6N. The peeling force of the positive electrode sheet can be 0.2N, 0.3N, 0.4N, 0.5N or 0.6N. Of course, the peeling force of the positive electrode sheet can be any point value within 0.2~0.6N, which will not be repeated here.
[0057] In another typical embodiment of the present application, a negative electrode sheet is provided, comprising a current collector and a negative electrode active coating, wherein the negative electrode active coating is prepared from a negative electrode slurry, and the negative electrode slurry comprises the above-mentioned negative electrode slurry.
[0058] The negative electrode sheet including the above-mentioned negative electrode slurry can inhibit volume expansion during charging and discharging, and has good rate performance and cycle performance. At the same time, the peeling force of the negative electrode sheet reaches 0.15~0.5N. The peeling force of the negative electrode sheet can be 0.15N, 0.25N, 0.35N, 0.45N or 0.5N. Of course, the peeling force of the negative electrode sheet can be any point value within 0.15~0.5N, which will not be repeated here.
[0059] In another typical embodiment of the present application, a lithium-ion battery is provided, including a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet includes the above-mentioned positive electrode sheet, and the negative electrode sheet includes the above-mentioned negative electrode sheet.
[0060] The lithium-ion battery comprising the positive electrode sheet and the negative electrode sheet has good electrochemical performance and cycle performance.
[0061] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.
[0062] Example 1
[0063] Preparation of positive electrode slurry: According to the weight percentage, 96.0 parts of recycled lithium iron phosphate, 1.5 parts of the first conductive carbon black, 2.0 parts of the first binder PVDF, 0.1 parts of the first dispersant polyester chain polymer HY-24000, 0.5 parts of the second dispersant polyvinyl pyrrolidone and 56mL of the first organic solvent N-methylpyrrolidone are first stirred at 1000rpm in a double planetary mixer to obtain a positive electrode slurry. Among them, the recycled lithium iron phosphate is a lithium iron phosphate material recycled by physical method, and the surface of the recycled lithium iron phosphate contains the third conductive carbon black and the third binder PVDF; the mass proportion of the third conductive carbon black in the recycled lithium iron phosphate is 0.5%, the mass proportion of the third binder PVDF is 2%, and the ratio of the mass of the recycled lithium iron phosphate to the volume of the first organic solvent N-methylpyrrolidone is 1.53g / mL.
[0064] Preparation of negative electrode slurry: According to the weight percentage, 96.0 parts of recycled graphite, 1.0 parts of the second conductive agent conductive carbon black, 2.0 parts of the second binder SBR, 1.5 parts of the first thickener CMC, the second organic solvent N-methylpyrrolidone and 96mL of deionized water were stirred for the second time at 800rpm in a double planetary mixer to obtain negative electrode slurry. Among them, the recycled graphite is a graphite material recycled by physical method, and the surface of the recycled graphite contains the fourth binder SBR and the second thickener CMC; the mass proportion of the fourth binder SBR in the recycled lithium iron phosphate is 0.1%, the mass proportion of the second thickener CMC is 1.6%, the mass ratio of the second organic solvent N-methylpyrrolidone and the recycled graphite is 0.3:100, and the mass ratio of the recycled graphite to the volume of deionized water is 1.02g / mL.
[0065] Example 2
[0066] Preparation of positive electrode slurry: According to the weight percentage, 97.0 parts of recovered lithium iron phosphate, 0.4 parts of the first conductive agent conductive carbon black, 1.5 parts of the first binder PVDF, 0.3 parts of the first dispersant polyacrylic acid, 0.3 parts of the second dispersant sodium dodecyl sulfate and 56mL of the first organic solvent N-methylpyrrolidone are first stirred at 300rpm in a double planetary mixer to obtain a positive electrode slurry. Among them, the recovered lithium iron phosphate is a lithium iron phosphate material recycled by physical method, and the surface of the recovered lithium iron phosphate contains the third conductive agent conductive carbon black and the third binder PVDF; the mass proportion of the third conductive agent conductive carbon black in the recovered lithium iron phosphate is 1%, the mass proportion of the third binder PVDF is 1.5%, and the ratio of the mass of the recovered lithium iron phosphate to the volume of the first organic solvent N-methylpyrrolidone is 1.51g / mL.
[0067] Preparation of negative electrode slurry: According to the weight percentage, 97.0 parts of recycled graphite, 2.0 parts of the second conductive agent conductive carbon black, 0.8 parts of the second binder SBR, 0.6 parts of the first thickener CMC, the second organic solvent ethylene glycol and 96 mL of deionized water were stirred for the second time at 300 rpm in a double planetary mixer to obtain negative electrode slurry. Among them, the recycled graphite is a graphite material recycled by physical method, and the surface of the recycled graphite contains the fourth binder SBR and the second thickener CMC; the mass proportion of the fourth binder SBR in the recycled lithium iron phosphate is 1%, the mass proportion of the second thickener CMC is 1%, the mass ratio of the second organic solvent ethylene glycol to the recycled graphite is 1:100, and the mass ratio of the recycled graphite to the volume of deionized water is 1.04 g / mL.
[0068] Example 3
[0069] Preparation of positive electrode slurry: According to the weight percentage, 99.0 parts of recovered lithium iron phosphate, 2.0 parts of the first conductive agent conductive carbon black, 0.4 parts of the first binder PVDF, 0.5 parts of the first dispersant polyoxyethylene ether, 0.1 parts of the second dispersant polyvinyl pyrrolidone and 56mL of the first organic solvent N-methyl pyrrolidone are first stirred at 1500rpm in a double planetary mixer to obtain a positive electrode slurry. Among them, the recovered lithium iron phosphate is a lithium iron phosphate material recycled by physical method, and the surface of the recovered lithium iron phosphate contains the third conductive agent conductive carbon black and the third binder PVDF; the mass proportion of the third conductive agent conductive carbon black in the recovered lithium iron phosphate is 1.5%, the mass proportion of the third binder PVDF is 0.8%, and the ratio of the mass of the recovered lithium iron phosphate to the volume of the first organic solvent N-methyl pyrrolidone is 1.82g / mL.
[0070] Preparation of negative electrode slurry: According to the weight percentage, 98.0 parts of recycled graphite, 0.4 parts of the second conductive agent conductive carbon black, 0.8 parts of the second binder SBR, 1.8 parts of the first thickener CMC, the second organic solvent dimethyl sulfoxide and 96 mL of deionized water were stirred for the second time at 1500 rpm in a double planetary mixer to obtain negative electrode slurry. Among them, the recycled graphite is a graphite material recycled by physical method, and the surface of the recycled graphite contains the fourth binder SBR and the second thickener CMC; the mass proportion of the fourth binder SBR in the recycled lithium iron phosphate is 2%, the mass proportion of the second thickener CMC is 0.1%, the mass ratio of the second organic solvent dimethyl sulfoxide and the recycled graphite is 1.5:100, and the mass ratio of the recycled graphite to the volume of deionized water is 1.06 g / mL.
[0071] Example 4
[0072] The difference from Example 1 is that in the preparation of the positive electrode slurry, the mass ratio of the first dispersant polyester chain polymer HY-24000 and the second dispersant polyvinyl pyrrolidone is 2.5:1.
[0073] Preparation of negative electrode slurry: The mass ratio of the second organic solvent N-methylpyrrolidone and the recovered graphite is 1.5:100, and finally the negative electrode slurry is obtained.
[0074] Example 5
[0075] The difference from Example 1 is that in the preparation of the positive electrode slurry, the mass ratio of the first dispersant polyester chain polymer HY-24000 and the second dispersant polyvinyl pyrrolidone is 3.5:1, and finally the positive electrode slurry is obtained.
[0076] Preparation of negative electrode slurry: The mass ratio of the second organic solvent N-methylpyrrolidone and the recovered graphite is 2.5:100, and finally the negative electrode slurry is obtained.
[0077] Example 6
[0078] The difference from Example 1 is that in the preparation of the positive electrode slurry: the ratio of the mass of the recovered lithium iron phosphate to the volume of the first organic solvent N-methylpyrrolidone is 2.51 g / mL, the first stirring speed is 1500 rpm, and finally the positive electrode slurry is obtained.
[0079] Preparation of negative electrode slurry: The ratio of the mass of recovered graphite to the volume of deionized water was 1.16 g / mL, the rotation speed of the second stirring was 1500 rpm, and finally the negative electrode slurry was obtained.
[0080] Example 7
[0081] The difference from Example 1 is that in the preparation of the positive electrode slurry: the ratio of the mass of the recovered lithium iron phosphate to the volume of the first organic solvent N-methylpyrrolidone is 3 g / mL, the first stirring speed is 250 rpm, and finally the positive electrode slurry is obtained.
[0082] Preparation of negative electrode slurry: The ratio of the mass of recovered graphite to the volume of deionized water was 1.5 g / mL, the rotation speed of the second stirring was 250 rpm, and finally the negative electrode slurry was obtained.
[0083] Example 8
[0084] The difference from Example 1 is that the solid content of the positive electrode slurry is 68%, and the solid content of the negative electrode slurry is 54%.
[0085] Example 9
[0086] The difference from Example 1 is that the solid content of the positive electrode slurry is 75%, and the solid content of the negative electrode slurry is 65%.
[0087] Comparative Example 1
[0088] Preparation of positive electrode slurry: According to weight parts, 96.0 parts of lithium iron phosphate, 1.5 parts of the first conductive agent conductive carbon black, 2.0 parts of the first binder PVDF, and 56 mL of the first organic solvent N-methylpyrrolidone were first stirred at 1000 rpm in a double planetary mixer to obtain a positive electrode slurry. Among them, lithium iron phosphate is a new material, and its surface does not contain a conductive agent and a binder.
[0089] Preparation of negative electrode slurry: According to the weight percentage, 96.0 parts of graphite, 1.0 parts of the second conductive agent conductive carbon black, 2.0 parts of the second binder SBR, 1.5 parts of the first thickener CMC and 96 mL of deionized water were stirred for the second time at 800 rpm in a double planetary mixer to obtain negative electrode slurry. Among them, graphite is a new material, and its surface does not contain a binder, a thickener and a conductive agent.
[0090] Comparative Example 2
[0091] The difference from Example 1 is that, in preparation of the positive electrode slurry: according to parts by weight, 96.0 parts of recovered lithium iron phosphate, 2.5 parts of the first conductive agent conductive carbon black, 2.5 parts of the first binder PVDF and 56 mL of the first organic solvent N-methylpyrrolidone are first stirred at 1000 rpm in a double planetary mixer to obtain a positive electrode slurry.
[0092] Preparation of negative electrode slurry: According to the weight parts, 96.0 parts of recycled graphite, 2.5 parts of the second conductive agent conductive carbon black, 2.5 parts of the second binder SBR, 2 parts of the first thickener CMC and 96 mL of deionized water were stirred for the second time at 800 rpm in a double planetary mixer to obtain negative electrode slurry.
[0093] Test method:
[0094] Preparation of positive electrode sheet: The positive electrode slurry of the above embodiment and comparative example is uniformly coated on the aluminum foil current collector, dried, cold pressed, and die-cut into strips to make positive electrode sheets.
[0095] Preparation of negative electrode sheet: The negative electrode slurry of the above embodiment and comparative example is uniformly coated on the copper foil current collector, dried, cold pressed, and die-cut into strips to form a negative electrode sheet.
[0096] The positive electrode sheet, negative electrode sheet and separator are made into a core package through a winding device, the core package is welded to the top cover assembly, loaded into an aluminum shell, and injected with lithium hexafluorophosphate solution electrolyte to form a battery cell. The battery cell then undergoes formation and capacity division processes during the charge and discharge process to obtain a lithium-ion battery.
[0097] Slurry viscosity test: measured using a rotational viscometer.
[0098] Slurry sedimentation rate test: using the solid content measurement method, the slurry is left to stand for 24 hours, the upper and lower slurries are baked, the slurries before and after drying are weighed, and the solid content and the solid content difference (i.e. 24h sedimentation) are calculated.
[0099] Stripping force test of the pole piece: Use a tensile testing machine to test the stripping force of the pole piece through the stripping test method.
[0100] Battery internal resistance test: Use a voltage internal resistance tester and test at 1kHz sinusoidal current.
[0101] Battery cycle capacity retention rate test: (1) Prepare a constant temperature and humidity test chamber and set its temperature to 25℃; select a battery and record its basic parameters such as appearance, size and weight; (2) Use high-precision charging and discharging equipment to perform the first charge and discharge cycle of the battery at a rate of 0.5C in an environment of 25℃. When charging, first charge at a constant current of 0.5C to 3.65V, then switch to constant voltage charging until the current drops below 0.05C, and leave it for 60 minutes; when discharging, discharge at a constant current of 0.5C to the battery cut-off voltage of 2.5V, leave it for 60 minutes, and record the capacity, voltage platform and other data of the first charge and discharge; (3) Perform a 0.5C charge and discharge cycle, and after the battery performance is stable, take the maximum discharge capacity in the first 10 cycles as the initial performance data; (4) The cycle test continues (such as 0.5C charging and discharging in step 2) until the battery capacity decays to a certain proportion of the initial capacity (such as 80% or 70%) or reaches the set maximum number of cycles. Capacity retention rate = 0.5C discharge capacity at the cycle number / initial discharge capacity.
[0102] The above test results are shown in Table 1 and Table 2.
[0103] Table 1
[0104]
[0105] Table 2
[0106]
[0107]
[0108] As can be seen from Table 1, the slurry performance of Example 1 using recycled lithium iron phosphate and recycled graphite has no significant difference in viscosity and 24h sedimentation rate from that of Comparative Example 1 using new active materials. As can be seen from Table 2, the peeling force of the positive and negative electrodes of Example 1 is better than that of Comparative Example 1, and the cycle performance of Example 1 is still at a relatively high level.
[0109] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0110] For lithium iron phosphate and graphite recovered by physical method, their surfaces still contain binders, and the binder on the surface of lithium iron phosphate can still exert most of the bonding properties under the condition of re-homogenization, and the binder on the surface of graphite can basically not exert its bonding properties. Therefore, the present application optimizes the composition and content of the positive electrode slurry and the negative electrode slurry so that the slurry can be stably settled and evenly dispersed during homogenization and coating, and is not prone to cracking during coating and baking. At the same time, in terms of performance, the positive electrode slurry and negative electrode slurry of the present application are basically the same as the slurry using new materials lithium iron phosphate and graphite, and have good compatibility on production equipment, which is conducive to resource recycling and reducing raw material costs. Specifically, in the positive electrode slurry, adding a dispersant can not only increase the steric hindrance between the lithium iron phosphate particles, thereby preventing the lithium iron phosphate particles from agglomerating, but also enhance the stability of the lithium iron phosphate particles and adjust the viscosity and fluidity of the positive electrode slurry, thereby helping to ensure the stability of the positive electrode slurry surface density during coating. Adding the second organic solvent to the negative electrode slurry can effectively separate the recycled graphite particles, thereby improving the dispersion uniformity of the recycled graphite and reducing the occurrence of cracking of the negative electrode sheet. At the same time, adding the second organic solvent can fully dissolve the second binder and make it evenly distributed around the recycled graphite particles and the second conductive agent, thereby enhancing the bonding force between the recycled graphite particles, preventing the pulverization and shedding of the negative electrode material, and thus extending the cycle life of the battery.
[0111] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An electrode slurry for a lithium iron phosphate battery, comprising a positive electrode slurry and a negative electrode slurry, each of which is independent of the other, wherein the positive electrode slurry comprises recycled lithium iron phosphate, and the negative electrode slurry comprises recycled graphite, wherein: The recycled lithium iron phosphate and the recycled graphite come from the scraps of the positive and negative electrodes of lithium iron phosphate batteries respectively; characterized in that: In parts by weight, the positive electrode slurry comprises: 96.0 to 99.0 parts of the recovered lithium iron phosphate; 0.4 to 2.0 parts of a first conductive agent; 0.4 to 2.0 parts of a first binder; 0.2 to 1.0 parts of a dispersant; and a first organic solvent; In parts by weight, the negative electrode slurry comprises: 96.0 to 98.0 parts of the recovered graphite; 0.4 to 2.0 parts of a second conductive agent; 0.8 to 2.2 parts of a second binder; 0.6 to 1.8 parts of a first thickener; and a second organic solvent and water.
2. The electrode slurry for lithium iron phosphate battery according to claim 1, characterized in that: The surface of the recycled lithium iron phosphate contains a third conductive agent and a third binder; the mass proportion of the third conductive agent in the recycled lithium iron phosphate is 0.5-1.5%, and the mass proportion of the third binder in the recycled lithium iron phosphate is 0.8-2%; And / or, the surface of the recycled graphite contains a fourth binder and a second thickener; the mass proportion of the fourth binder in the recycled graphite is 0.1-2%, and the mass proportion of the second thickener in the recycled graphite is 0.1-1.6%.
3. The electrode slurry for lithium iron phosphate battery according to claim 1 or 2, characterized in that: The solid content of the positive electrode slurry is 56-68%, and / or the solid content of the negative electrode slurry is 48-54%; And / or, after the positive electrode slurry and the negative electrode slurry are respectively left to stand for 24 hours, the viscosity of the positive electrode slurry is 240000-400000 mPa·s, and the sedimentation rate of the positive electrode slurry is ≤4%, and / or, the viscosity of the negative electrode slurry is 3000-8000 mPa·s, and the sedimentation rate of the negative electrode slurry is ≤1.5%.
4. The electrode slurry for lithium iron phosphate battery according to claim 2, characterized in that: The first conductive agent and the third conductive agent are each independently selected from any one or more of conductive carbon black, acetylene black and carbon nanotubes; the first binder and the third binder are each independently selected from polyvinylidene fluoride and / or polyvinyl butyral; And / or, the dispersant includes a first dispersant and a second dispersant, the first dispersant is selected from any one or more of polyacrylic acid, polymethacrylic acid, polyester chain polymer, sodium silicate, polyoxyethylene ether, glycerol, sodium alginate and hydroxypropyl methylcellulose; the second dispersant is selected from any one or more of polyethylene glycol, sodium lauryl sulfate, polyvinyl pyrrolidone and polyurethane compounds; and / or, the mass ratio of the first dispersant to the second dispersant is 1 to 2.5:
1.
5. The electrode slurry for lithium iron phosphate battery according to claim 2, characterized in that: The second conductive agent is selected from any one or more of conductive carbon black, acetylene black and carbon nanotubes; and / or the second binder and the fourth binder are each independently selected from any one or more of styrene-butadiene rubber, polyacrylic acid and waterborne polyurethane; and / or the first thickener and the second thickener are each independently selected from any one or more of carboxymethyl cellulose, hydroxyethyl cellulose and polyvinyl alcohol; and / or, the second organic solvent is selected from any one or more of N-methylpyrrolidone, ethylene glycol, ethylene glycol ether compounds, dimethyl sulfoxide and propylene carbonate; and / or, the mass ratio of the second organic solvent to the recovered graphite is 0.3-1.5:100; And / or, the first organic solvent is N-methylpyrrolidone.
6. A method for preparing the electrode slurry for lithium iron phosphate battery according to any one of claims 1 to 5, characterized in that: The method for preparing the positive electrode slurry comprises: first stirring raw materials including recycled lithium iron phosphate, a first conductive agent, a first binder, a dispersant and a first organic solvent to obtain the positive electrode slurry; The method for preparing the negative electrode slurry comprises: subjecting raw materials including recycled graphite, a second conductive agent, a second binder, a first thickener, a second organic solvent and water to a second stirring to obtain the negative electrode slurry.
7. The preparation method according to claim 6, characterized in that: The ratio of the mass of the recovered lithium iron phosphate to the volume of the first organic solvent is 1.37 to 2.51 g / mL; and / or the ratio of the mass of the recovered graphite to the volume of the water is 0.92 to 1.16 g / mL; And / or, the rotation speeds of the first stirring and the second stirring are independently 300 to 1500 rpm.
8. A positive electrode sheet, comprising a current collector and a positive electrode active coating, wherein the positive electrode active coating is prepared from a positive electrode slurry, characterized in that: The positive electrode slurry includes the positive electrode slurry according to any one of claims 1 to 5.
9. A negative electrode sheet, comprising a current collector and a negative electrode active coating, wherein the negative electrode active coating is prepared from a negative electrode slurry, characterized in that: The negative electrode slurry includes the negative electrode slurry according to any one of claims 1 to 5.
10. A lithium ion battery comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The positive electrode sheet includes the positive electrode sheet according to claim 8, and the negative electrode sheet includes the negative electrode sheet according to claim 9.
Citation Information
Patent Citations
Method for recovering lithium-ion battery cathode materials
CN101570347A
Method for recycling lithium iron phosphate wastes in manufacturing link of lithium iron phosphate batteries
CN104362408A
Lithium ion battery raw material recycling method and method for reproducing battery by utilizing recycled material
CN111180820A
Method for directly recycling lithium iron phosphate in waste lithium iron phosphate battery
CN111792633A
Preparation method of low-cost negative electrode graphite
CN115353102A